2006
DOI: 10.1002/ijc.22118
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐germline gene expression in pediatric solid tumors using quantitative real‐time PCR

Abstract: Cancer-germline genes (CGGs) code for immunogenic antigens that are present on various human tumors but not on normal tissues. The importance of CGGs in cancer immunotherapy has led to detailed studies of their expression in a range of human tumors. We measured the levels of expression of 12 CGGs in various pediatric solid tumors to identify targets for therapeutic cancer vaccines. Quantitative real-time PCR (qPCR) was used to measure the expression of 8 MAGE genes and of genes LAGE-2/NY-ESO-1 and GAGE-1, 2, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 48 publications
(47 reference statements)
0
48
0
Order By: Relevance
“…A number of studies have investigated the detection of cancer germ line genes (CGGs) both in pediatric sarcomas (3) and pediatric brain tumors (4). The discovery of global antigens for tumor vaccines could become salvatory for childhood malignancies (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have investigated the detection of cancer germ line genes (CGGs) both in pediatric sarcomas (3) and pediatric brain tumors (4). The discovery of global antigens for tumor vaccines could become salvatory for childhood malignancies (3).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of global antigens for tumor vaccines could become salvatory for childhood malignancies (3). Other studies have reported the common appearance of antigens in Ewing's sarcoma/primitive neuroectodermal tumor (EWS/PNET) with lymphoblastic lymphoma (5).…”
Section: Introductionmentioning
confidence: 99%
“…46,47 Among the large family of TAAs, expression of cancer testis antigens (NY-ESO, MAGE-A3, MAGE-A4, PRAME, and LAGE) occurs in a variety of sarcomas, including synovial sarcomas, myxoid round-cell liposarcoma, osteosarcoma, ES, chondrosarcoma, leiomyosarcoma, and UPS. [48][49][50] Nevertheless, and as expected for such a heterogeneous group of tumors, immunogenicity is not uniform among sarcomas, and can be influenced by the tumor genomic landscape or mutational load. Across different histologies, and particularly in melanoma and non-small cell-lung cancer, increased number of somatic missense mutations and mutational epitopes have been associated with patient survival and benefit from both anti-CTLA-4 and anti-PD-1 agents, 57 High levels of somatic copy number alterations (aneuploidy) have been shown to correlate with total number of mutations, elevated markers of cell cycle/proliferation, reduced expression of markers for cytotoxic immune cell infiltrates, and poorer prognosis in melanoma patients treated with anti-CTLA therapy, supporting the concept that aneuploidy is involved in mechanisms of cell proliferation and immune evasion.…”
Section: Tumor Antigens and Intrinsic Antigenic Potential In Sarcomasmentioning
confidence: 99%
“…CTAs comprise 70 families with over 140 antigens. 12,73 Their biologic function is not fully understood, but because of their immunogenicity they are being studied as T cell targets for vaccine and adoptive cellular therapy. However, not all antigens are immunogenic in all patients and expression of the antigens may vary between patients.…”
Section: Dendritic Cell Based Vaccinesmentioning
confidence: 99%